1980
DOI: 10.1093/bja/52.9.893
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tubocurarine Administered by Combined I.V. Bolus and Infusion

Abstract: Pharmacokinetic data were used to calculate an i.v. bolus dose and infusion regimen for tubocurarine (dtc). This produced continuous paralysis in 12 anaesthetized patients. In nine of the patients the duration of infusion was sufficient to achieve a "steady-state" dtc concentration in the plasma (mean 1.09 microgram ml-1). At the completion of the infusion, twitch response had been abolished in half of the group, but 30 min later all had a measurable response. All plasma concentrations decreased rapidly after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Steady state rates of infusion in the sheep for 80%paralysis.With reference to the entry for d-tubocurarine in the Table, note that a predicted figure of 2. 7 ~g/kg/min is reported by Ramzan et al5 when infusing d-tubocurarine in man with 95% paralysis of the adductor pollicis muscle. A measurement additional to the results shown in the Table demonstrates a steady state infusion rate in the sheep of 0.7 ~g/kg/min for 95% paralysis of the rectus abdominus muscle.…”
mentioning
confidence: 75%
“…Steady state rates of infusion in the sheep for 80%paralysis.With reference to the entry for d-tubocurarine in the Table, note that a predicted figure of 2. 7 ~g/kg/min is reported by Ramzan et al5 when infusing d-tubocurarine in man with 95% paralysis of the adductor pollicis muscle. A measurement additional to the results shown in the Table demonstrates a steady state infusion rate in the sheep of 0.7 ~g/kg/min for 95% paralysis of the rectus abdominus muscle.…”
mentioning
confidence: 75%
“…This is performed using the in vitro value for KB and using the relationship: this degree of paralysis (from Table 3) allowed estimation of the amount of drug bound to plasma protein (see also 25 at a dTc concentration of 5 Ilg/ml, when one considers that these calculations were based on non steady state values. Ramzan et al 9 reported a steady state concentration of dTc of 1.09Ilg/ml corresponding to 95 per cent paralysis, and if this value for the total concentration of dTc is used then a value of 45 per cent for the degree of binding of dTc to plasma protein is obtained.…”
Section: Relationship Between Muscle Relaxant-receptor Dissociation Cmentioning
confidence: 99%